Synthesis of 3-azidopiperidine skeleton employing ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether: total synthesis of d-2 receptor agonist (+/-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Lasonkar, Pradeep B.; Gonnade, Rajesh G. (Organic letters, 2018)
The total synthesis of (+/-)-quinagolide, which is a D-2 receptor agonist, was accomplished via a ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether route. Key features of the synthesis include Claisen rearrangement, PPTS (pyridinium p-toluene-sulfonate)-catalyzed one-pot acetal deprotection, followed by a diastereoselective Henry reaction, which enables construction of the required trans ring junction and CAN-mediated regioselective azidoalkoxylation of enol ether. The PPTS-catalyzed intramolecular diastereoselective Henry reaction to fix three contiguous stereocenters on tetrahydronaphthalene and the first-of-its-kind synthesis of the 3-azidopiperidine skeleton, using a CAN -mediated regioselective azidoalkoxylation of enol ether, are important findings of the present work.